URGENSI PENGATURAN FINANCIAL TECHNOLOGY DI INDONESIA - Elvira Fitriyani Pakpahan; Kristina Chandra; Anderson Tanjaya (Jurnal Darma Agung, 2020)
Fintech is a combination of a financial system with digital technology. Fintech's goal is to provide financial services by making use of modern software and technology. This type of research is normative juridical research. The nature of descriptive research. Qualitative data analysis. Based on the results of the research that the existence of urgency will provide clarity on the competitive space and legal Fintech climate. The existing Fintechs really understand the problems they are facing. For this reason, the clarity of the urgency of Fintech regulation can further convince the public that their interests are well protected. Therefore, the government issued the urgency of regulating Financial Technology in Indonesia, including the Financial Services Authority Regulation (POJK), Law Number 8 of 1999 concerning Consumer Protection (UUPK), Law Number 21 of 2008 concerning Banking, Law Number 19 2016 Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, Government Regulation Number 71 of 2019 concerning Electronic Systems and Transactions.